The impact of stress related disorders on quality of life - Čolović, Olga (Array, 2009)
Some new studies have shown a significant connection between post-traumatic stress disorder and impairment of the quality of life (QoL), whereas, to our knowledge, research on the connection between other disorders of the stress related group and quality of life do not exist. We studied the quality of life in 160 subjects who have experienced certain stressogenic life events. Within the first group (80 subjects) a certain stress related disorder was diagnosed after a stressogenic life event. In the second group none of the stress related disorders was developed after a stressogenic life event